Internet for the people : the fight for our digital future - Tarnoff, Ben, (London; New York: Verso, 2022)
"Ben Tarnoff issues a rallying cry for a new, democratic internet. This means deprivatizing the network to create an internet where people, and not profit, rule"-- Includes bibliographical references and index. Preface: Among the Eels -- A People's History of the Internet -- The Plunder Continues -- The People's Pipes -- From Below -- Up the Stack -- Online Malls -- Elastic Empires -- Inclusive Predators -- Toward the Forest -- Conclusion: Future Nostalgia. "Ben Tarnoff issues a rallying cry for a new, democratic internet. This means deprivatizing the network to create an internet where people, and not profit, rule"--